Defect Modulation Doping. (10th February 2019) - Weidner, Mirko; Fuchs, Anne; Bayer, Thorsten J. M.; Rachut, Karsten; Schnell, Patrick; Deyu, Getnet K.; Klein, Andreas
Abstract: The doping of semiconductor materials is a fundamental part of modern technology, but the classical approaches have in many cases reached their limits both in regard to achievable charge carrier density as well as mobility. Modulation doping, a mechanism that exploits the energy band alignment at an interface between two materials to induce free charge carriers in one of them, is shown to circumvent the mobility restriction. Due to an alignment of doping limits by intrinsic defects, however, the carrier density limit cannot be lifted using this approach. Here, a novel doping strategy using defects in a wide bandgap material to dope the surface of a second semiconductor layer of dissimilar nature is presented. It is shown that by depositing an insulator on a semiconductor material, the conductivity of the layer stack can be increased by 7 orders of magnitude, without the necessity of high‐temperature processes or epitaxial growth. This approach has the potential to circumvent limits to both carrier mobility and density, opening up new possibilities in semiconductor device fabrication, particularly for the emerging field of oxide thin film electronics. Abstract : Defect modulation doping allows for manipulation of the Fermi energy at interfaces. The combination of dissimilar materials relaxes the constraint of epitaxial film growth and broadens the application of modulation doping to low‐temperature deposition techniques. Intrinsic defect formation can then be kinetically suppressed, which opens the potential to overcome classical doping limits.